Twenty-seven Major American Symphony Orchestras A History and Analysis of Their Repertoires, Seasons 1842-43 through 1969-70 - Mueller, Kate Hevner (Indiana University Press, 1973)
Twenty-seven Major American Symphony Orchestras: A History and Analysis of Their Repertoires, Seasons 1842-43 through 1969-70 surveys the the performances of American symphonies, described in the author's 1973 introduction to the text as follows: "This study of orchestra repertoires is one more contribution to the history of American music. . . .The present study . . . provide[s] the basic data for every composition through 130 years, 1840-1970 with its performance time in minutes and the dates of all performance, together with the name of its composer, his life span and national origin. A few charts are also offered to indicate the general trends, and from these data other scholars will be able to uncover more significant facts and theories about this most important institution in our American musical culture.